Prevalence of metabolic syndrome in adolescents living in Mthatha, South Africa - Sekokotla MA; Goswami N; Sewani-Rusike CR; Iputo JE; Nkeh-Chungag BN (Dove Medical Press, 2017)
Morongwe Annah Sekokotla,1 Nandu Goswami,2 Constance Rufaro Sewani-Rusike,1 Jehu Erapu Iputo,3 Benedicta Ngwenchi Nkeh-Chungag4 1Department of Human Biology, Faculty of Health Sciences, Walter Sisulu University, Mthatha, South Africa; 2Gravitational Physiology and Medicine Research Unit, Institute of Physiology, Medical University of Graz, Graz, Austria; 3Department of Medical Education, Faculty of Health Sciences, Walter Sisulu University, 4Department of Biological and Environmental Sciences, Faculty of Natural Sciences, Walter Sisulu University, Mthatha, South Africa Objective: Metabolic syndrome (MetS), defined as the clustering of three of five risk factors (hypertension, obesity, triglyceridemia, dyslipidemia and hyperglycemia), is being increasingly mentioned among children and adolescents despite there being no consensus on how it should be defined in this set of population. Furthermore, very few studies have focused on MetS in children and adolescents in sub-Saharan populations. This study, therefore, aimed at determining the prevalence of the MetS and contributing risk in adolescents living in Mthatha, South Africa.Research design and methods: Four hundred and ten adolescents (age range: 13–18 years, both sexes) were recruited into this cross-sectional study. In addition to a lifestyle questionnaire being administered, anthropometric measurements (weight, height and waist circumferences) were carried out for each participant. Fasting venous blood was collected for lipid profile and blood glucose assessments. Blood pressure was also measured. MetS was assessed using appropriate diagnostic criteria for children and adolescents.Results: Complete data sets were collected from 371 participants. Females showed an elevation in the risk factors for MetS. Of the 371 participants, 40.2% were overweight/obese (47.5% females; 22.5% males). MetS was diagnosed in 3.1% female participants compared with 6.0% in male participants.Conclusions: More risk factors for the MetS are seen among the overweight/obese as compared to lean adolescents. Given the fact that childhood overweight/obesity often continues into adulthood, it is important to address the causes of increased risk for MetS earlier in life to prevent the development of disease in adult life. Keywords: metabolic syndrome, adolescent health, overweight, obesity